Monitoring Rice Stem Borer, Chilo Polychrysus (Lepidoptera: Crambidae) And Insecticidal Activity Of Selected Insecticides - Mohd Khari, Nur Atiqah (2021)
Monitoring of rice stem borer insecticidal activity has been initiated by studying the abundance and infestation level of rice stem borer in MADA area, constructing the life table of Chilo polychrysus and determining the insecticdal efficacy of selected commercial insecticides towards C. polychrysus in the glasshouse. The study revealed that Region 3 (Hutan Kampung, Tajar and Pendang) was the most highly infested by rice stem borer followed by Region 4, Region 2 and Region 1. Among the three districts evaluated in Region 3, Pendang suffered the highest rice stem borer infestation at specific location, Pendang B with 20.53% of infestation. Season one (November to February) recorded the greatest infestation during the vegetative stage of the rice plant with 30.83% of dead heart. The rice stem borer was observed to infest at optimum level with lower value of RHmax (80.0%), higher Tdiff (32.8oC) and lower amount of rainfall (0.6mm). Three species were found at all four regions in MADA and that were Chilo polychrysus (black-headed stem borer), Sesamia inferens (pink stem borer) and Scripophaga incertulas (yellow stem borer). Chilo polychrysus (black-headed stem borer) was once a predominant species of rice stem borer in Malaysia and have became dominant in this study at Region 1.